Estudio de factibilidad para la creación de una empresa productora y comercializadora de artesanías elaboradas a base de materiales reciclados (como plástico, metal, papel, sobrantes de tela y madera) en el municipio de la Tebaida Quindío (2013)
Babalú is an innovative business idea that is focused on contemporary handicrafts production and marketing. These are made of recyclable materials such as plastic, paper and metal, and it will be located in La Tebaida, Quindío. This idea came up to take advantage of different materials that usually become garbage, and that can be exploit as raw material taking into account their long process of disintegration. In this way, the project aim to show the great profits from handicrafts made of recyclable materials. The crafts have a big demand in the department since it is the second most important tourist destination of Colombia, and coffee cultural landscape world heritage. Thus, this business idea stands out in the craft and tourist sector of the department because it is very important in the economic development of it. Besides, it contributes to the economic and social growth thanks to the big amount of tourists that arrive in the department of Quindío. These among other reasons, make the tourists be the objective market of the product. Finally, research was very important in order to determine the viability of the project. It was necessary in order to establish the strengths, the opportunities, the threats and weaknesses of this business idea. The investigation was divided into different stages. The first one was the market study. Through this, the objective market, the supply and demand, and the prizes of commercialization were identified. The second one was the technical and administrative study. This helped to identify the plant distribution, the consolidation of flow process, the location, the staff and the function manual. The last one was the financial study. This evaluated the technical and market aspects in unit of currency. It showed that this project is not only viable, but also profitable and sustainable.